Overview of Piezoelectric Biosensors, Immunosensors and DNA Sensors and Their Applications - Pohanka, Miroslav (Materials (Basel, Switzerland), 2018)
Piezoelectric biosensors are a group of analytical devices working on a principle of affinity interaction recording. A piezoelectric platform or piezoelectric crystal is a sensor part working on the principle of oscillations change due to a mass bound on the piezoelectric crystal surface. In this review, biosensors having their surface modified with an antibody or antigen, with a molecularly imprinted polymer, with genetic information like single stranded DNA, and biosensors with bound receptors of organic of biochemical origin, are presented and discussed. The mentioned recognition parts are frequently combined with use of nanoparticles and applications in this way are also introduced. An overview of the current literature is given and the methods presented are commented upon.
Keywords: biosensor; acoustic sensor; piezoelectric; QCM; oscillation; immunosensor; anisotropy; label free; quartz crystal microbalance; affinity